Glucagon-like peptide-1 receptor agonist exendin 4 ameliorates diabetes-associated vascular calcification by regulating mitophagy through the AMPK signaling pathway - Kui Chen; Hao-jie Jin; Zi-heng Wu; Bao-fu Zhang; Jun Wu; Zi-yi Huang; Ying-peng Huang; Xin-wu Lu; Xiang-tao Zheng (BMC, 2024)
Abstract Background Vascular calcification (VC) is a complication in diabetes mellitus (DM) patients. Osteogenic phenotype switching of vascular smooth muscle cells (VSMCs) plays a critical role in diabetes-related VC. Mitophagy can inhibit phenotype switching in VSMCs. This study aimed to investigate the role of the glucagon-like peptide-1 receptor (GLP-1R) agonist exendin 4 (EX4) in mitophagy-induced phenotype switching. Materials and methods The status of VC in T2DM mice was monitored using Von Kossa and Alizarin Red S (ARS) staining in mouse aortic tissue. Human aortic smooth muscle cells were cultured in high glucose (HG) and β-glycerophosphate (β-GP) conditioned medium. Accumulation of LC3B and p62 was detected in the mitochondrial fraction. The effect of EX4 in vitro and in vivo was investigated by knocking down AMPKα1. Results In diabetic VC mice, EX4 decreased the percentage of von Kossa/ARS positive area. EX4 inhibited osteogenic differentiation of HG/β-GP-induced VSMCs. In HG/β-GP-induced VSMCs, the number of mitophagosomes was increased, whereas the addition of EX4 restored mitochondrial function, increased the number of mitophagosome-lysosome fusions, and reduced p62 in mitochondrial frictions. EX4 increased the phosphorylation of AMPKα (Thr172) and ULK1 (Ser555) in HG/β-GP-induced VSMCs. After knockdown of AMPKα1, ULK1 could not be activated by EX4. The accumulation of LC3B and p62 could not be reduced after AMPKα1 knockdown. Knockdown of AMPKα1 negated the therapeutic effects of EX4 on VC of diabetic mice. Conclusion EX4 could promote mitophagy by activating the AMPK signaling pathway, attenuate insufficient mitophagy, and thus inhibit the osteogenic phenotype switching of VSMCs.